Effect of Parasitic Infection on Glucose and Lipase of Host Pigeon (Columba livia) Tissues - Shazia Nisar; M. Farhanullah Khan; M. Arshad Azmi (Journal of Basic & Applied Sciences, 2012)
The aim of the study was to observe parasitic effect on lipase and glucose content in the tissue of artificially infested host pigeon with cestode parasites. Gastro-intestinal tract associated organs were extracted from the body cavity of dissected animal. Gizzard, liver, spleen, pancreas were separated and preserved. Thereafter, Lipase and glucose determination was carried out from these organs. It was observed that parasitic infection decreased lipase in liver and spleen while increased in pancreas. Higher lipase content was measured in infected animal’s crop a lesser content was measured in gizzard. It was also observed that infection impaired glucose level in intestine and other organs as well. Parasitic infections enhanced the glucose level in intestine and crop, while decreased glucose level in spleen, pancreas and liver.